Widowhood of elderly Filipino males stressors, challenges and coping strategies - Mendoza, Christiana Michele B.; Santoalla, Ariana Luna Isabel C.; Tongson, Excelsa C. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT This study identified the stressors and described the challenges and coping strategies that elderly Filipino widowed males encountered in their widowhood. Six elderly Filipino widowers residing in Metro Manila and in Bulacan were identified through snowball sampling. Data were gathered through in-depth interviews, were transcribed, and presented in cases. Two themes were identified as stressors namely loneliness and sadness. There were five themes for challenges namely relationship with family, health, financial concerns, living alone, and difficulty accepting wife?s death. Lastly, there were nine themes that emerged for coping strategies namely faith and religion, redirection of mindset, acceptance of the situation, seeking companionship, social support, keeping busy, travelling, reminiscing about wife and personal care. Future researches may consider a bigger sample size to gather more information about the experiences and overall situation of the elderly widowers in the Philippines as well as younger widowers with dependent children.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Stress in old age -- Philippines; Stress management for older people -- Philippines; Widowhood -- Philippines